Defensive patterns of chestnut genotypes (Castanea spp.) against the gall wasp, Dryocosmus kuriphilus - Lombardero, María J.; Ayres, Matthew P.; Álvarez-Álvarez, Pedro; Castedo-Dorado, Fernando (Frontiers in Forests and Global Change, 2022)
Plants draw from various genetically controlled defenses to protect against herbivores and pathogens. The efficacy of alternative defenses can vary with the biology and phylogeny of the enemy. Dryocosmus kuriphilus, an invasive gall maker native to China, has become one of the main pests of chestnut trees around the world. We studied genetic variation in resistance and susceptibility to D. kuriphilus within a replicated blocked planting of 12 chestnut genotypes established in Galicia, Spain in 2004. We found very high genetic variation in susceptibility to D. kuriphilus. We evaluated if the variation was due to host selection by the wasp, differential efficacy of inducible defenses in the trees, or variability in susceptibility of the plant to manipulation by the gallmaker. We assessed host selection by counting number of eggs laid by females in tree buds and comparing preferences with phytochemistry. We also measured inducible changes in phytochemistry within and around galls, gall physical characteristics, parasitism, and insect fitness. The effective defense mechanisms in resistant genotypes involved (1) hypersensitive reactions to eggs or neonates within buds and (2) early precise abscission of nascent galls from expanding leaves. Surprisingly, the genetic resistance to D. kuriphilus of the chestnut genotypes we tested was not related to phenols, terpenes, and primary nutrition.